Photo assisted negative differential resistance in porous silicon: A potential nano-structure for hot carrier solar cell. (2021) - Biswas, Susmita; Nandi, Anupam; Basu, Shayari; Chakrabarty, Sudipta; Mukhopadhyay, Sumita; Saha, Hiranmay; Hossain, Syed Minhaz
Abstract: A device, supporting negative differential resistance, has been fabricated. Aluminum top contacts have been deposited on electrochemically synthesized porous silicon layer on p-type silicon substrate for this purpose. Top-bottom DC current vs. voltage (I-V) characteristics of the fabricated device have been recorded at room temperature under dark condition and injecting photons. Dark I-V characteristics of this device indicate the presence of negative differential resistance (NDR). Similar kind of I-V characteristics has been observed under illumination. At the same time, fabricated device shows photovoltaic effect after injecting photons. This may be due to some series and parallel combination of multiple junctions with photovoltaic nature.